Analysis of Anaemia Incidence in Pregnant Women - Nurul Rahma; Ratna Dewi; Dina Anggraini (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2025)
In Indonesia, the prevalence of anaemia among pregnant women is 37%, indicating that the incidence of anaemia among pregnant women is still relatively high. In Bengkulu, Jembatan Kecil Health Centre recorded the highest number of anaemic pregnant women, 27. The purpose of this study was to determine the relationship between age, knowledge, Fe tablet consumption compliance, and class participation of pregnant women with the incidence of anaemia. This research method used an analytical survey with a cross sectional design. The sampling technique was done by total sampling, involving 93 pregnant women. There was a significant relationship between age, knowledge, Fe tablet consumption, and classes of pregnant women with the incidence of anaemia in third trimester pregnant women, with a p value = 0.001. Adherence to Fe tablet consumption was the variable that most influenced the incidence of anaemia in third trimester pregnant women with the highest Exp(B) value of 56.875. This study concluded that there is a relationship between age, knowledge, adherence to Fe tablet consumption, and activeness of pregnant women's classes with the incidence of anaemia in pregnant women at Jembatan Kecil Health Centre in 2024. It is expected that health workers monitor Fe tablet consumption through family empowerment and health cadres.